Automated Mixing Process for Solar Powered Fertigation System Using IoT Application - Azman, Muhammad Syafiq; Jumaat, Siti Amely; Ismail, Muhammad Nafis; Salimin, Suriana; Mohamad Nor, Ahmad Fateh (Journal of Electronic Voltage and Application, 2023)
The rising population globally, along with the need to maintain sustainable food production, has increased demand for efficient agricultural practices. Fertigation is the combination of fertilization with irrigation, has emerged as an effective method for increasing harvests while using less resources. The problem of traditional method are inefficiency and inaccuracy of manual fertilization methods in agriculture. The traditional methods of fertilization rely on manual application of fertilizers, which can be time- consuming and labor-intensive. Additionally, manual methods can lead to over- or under-fertilization, which can negatively impact plant growth and yield. As a solution, an automated mixing process for fertigation system powered by solar using IoT application was developed to solve the problem. This system can be controlled using a smartphone and all the process from flowing the fertilizer to a mixture tank and watering the plant can be automatically implemented. The nutrient for each type of plant can be established using Blynk application such that the plant could grow properly. This prototype can also help the user monitor the level of fertilizer in the tank in which the user gets a message from the smartphone if the fertilizer level is decreased or low. The data collected is the time taken by the system to mix the setup value of the solution using Electrical Conductivity (EC) sensor. It can be concluded that if the setup EC value in Blynk is large, the time taken to mix the solution increases. Another result is monitoring the fertilizer level of fertilizer in two tanks. In this case, the ultrasonic sensor detects the distance of fertilizer in both tanks and if the level of fertilizer in the tank is low, a notification will appear in Blynk application, stating that the tank level is low. All the output from this system is proven to be successful in this work.